Non-invasive real-time prediction of inner knee temperatures during therapeutic cooling. Issue 2 (November 2015) - Rashkovska, Aleksandra; Kocev, Dragi; Trobec, Roman
Highlights Non-invasive real-time prediction of inner body temperature variables during cryotherapy. Validated simulation model of the cryotherapeutic treatment. Machine learning methods on the simulated data to construct a predictive model. Feature ranking with the RReliefF method. Using only skin temperatures as input attributes gives excellent prediction.